Beautify your garden with variegated Spathiphyllum - Patil, Manjunath S.; Karale, Anil R.; Gaikwad, Dattaraya T. (Indian Horticulture, 2019)
A spontaneous mutant of Spathiphyllum cochlearispathum Schott. with variegated leaves has been located in ex situ conservatory of College of Horticulture, Pune. The mutant was collected and established in the nursery. It has been monitored for the last five successive years and confirmed that the mutant retained its variegated leaf character. The variegation does not affect the normal shape of leaf. The presence or absence of chlorophyll and/or carotenoids as in white or yellow variegates was noted. The variegated mutant form a new addition to the world list of genus and to the garden ornamentals.